Rigorous state-based methods : 7th International Conference, ABZ 2020, Ulm, Germany, May 27-29, 2020, Proceedings /: 7th International Conference, ABZ 2020, Ulm, Germany, May 27-29, 2020, Proceedings. (2020) - Unknown
No abstract available